Thy-1 Regulates VEGF-Mediated Choroidal Endothelial Cell Activation and Migration: Implications in Neovascular Age-Related Macular Degeneration - Wang, Haibo; Han, Xiaokun; Kunz, Eric; Hartnett, M. Elizabeth (Investigative ophthalmology & visual science, 2016)
This study addresses the hypothesis that age-related stresses upregulate Thy-1 in choroidal endothelial cells (CECs) and contribute to CEC activation and migration, processes important in choroidal neovascularization (CNV). Measurements were made of Thy-1 protein (Western blot) in CECs and Thy-1 mRNA (real time quantitative PCR) in CECs treated with VEGF, CCL11, or PBS or in RPE/choroids from young or old donors or lasered or nonlasered mice. Immunolabeled Thy-1 in ocular sections was compared from young versus old human donor eyes or those with or without neovascular AMD or from lasered versus nonlasered mice. Choroidal endothelial cells transfected with Thy-1 or control siRNA or pretreated with Thy-1 blocking peptide or control were stimulated with VEGF or 7-ketocholesterol (7-KC). Choroidal endothelial cell migration, proliferation, cytoskeletal stress fibers, Rac1 activation, and phosphorylated VEGF receptor 2 (VEGFR2), integrin β3, and Src were measured. Statistics were performed using ANOVA. Thy-1 was expressed in retinal ganglion cells and in vascular endothelial-cadherin-labeled choroid and localized to human or mouse laser-induced CNV lesions. Thy-1 protein and mRNA were significantly increased in CECs treated with VEGF or CCL11 and in RPE/choroids from aged versus young donor eyes or from lasered mice versus nonlasered controls. Knockdown or inhibition of Thy-1 in CECs significantly reduced VEGF-induced CEC migration and proliferation, stress fiber formation and VEGFR2, Src, integrin β3 and Rac1 activation, and 7-KC-induced Rac1 and Src activation. Thy-1 in CECs regulates VEGF-induced CEC activation and migration and links extracellular 7-KC to intracellular signaling. Future studies elucidating Thy-1 mechanisms in neovascular AMD are warranted.